Anticancer activity of ShivanarvembuKuzhi Thailam: An in-vitro study - ARUN D,; DR.SARASWATHI U, (International Journal of Pharma and Bio Sciences, 2017)
ShivanarVembuKuzhiThailam (SVKT) is a poly herbal siddha drug used for the skin care ailments. The aim of the current study is to evaluate the anticancer activity of SVKT in the skin cancer cell lines. The cytotoxic effect of SVKT was studied on the two skin cancer cell lines namely human squamous carcinoma cell line (A431) and murine melanoma cell line (B16F10). The results reveals that the SVKT is effective in killing the A431 cancer cells when compare to B16F10 cells. Further the gene expression studies were conducted in A431 cancer cells. Expression levels of genes such as Bcl-2, COX-2, p53 and MMP-9 were monitored. From the results, it can be inferred that the SVKT, upregulates the expression tumor suppressor gene p53 and down regulates the other regulatory genes such as Bcl-2, COX-2 and MMP-9.